Kolokasi Bahasa Berbentuk Al-Ma’thuf dan Al-Ma’thuf A’laihi: Kata Iman dan Amal Shalih dalam Al-Quran - Irhamni, Muhammad Adam Ali Fikar (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
The Qur'an is considered a miracle and is believed to contain I'jaz Bayani, a kind of linguistic and literary excellence that is present in every word, sentence, sound, verse, and letter. One way to identify I'jaz Bayani in the Qur'an is to explore the connection between the words "iman" (faith) and "good deeds." There is a need for this exploration because currently, faith is often only understood within the context of aqidah (the six pillars of faith). Many Muslims tend to focus only on a limited concept of faith, believing that it is solely about the belief in Allah SWT., His messengers, His books, His angels, and destiny. However, the Qur'an and hadiths mention that faith is closely linked to righteous deeds and good morals. If we examine the Qur'an, we will consistently find that faith and good deeds are mentioned together. This study uses a descriptive method that involves collecting data and verses related to faith and good deeds, followed by an analysis of interpretations and meanings from various sources. The aim of this research is to identify aspects of Ijaz Bayani in the relationship between faith and good deeds in the Qur'an and its semantics. The results indicate that the frequent mention of faith and good deeds in the Qur'an emphasizes the connection, compatibility, and confirmation between the two. Allah chose to associate the words "good deeds" with faith to emphasize their relationship.